PENGARUH GOOD CORPORATE GOVERNANCE, KINERJA KEUANGAN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Berliani, Citra; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to test the influence of good corporate governance, financial performance, and firm size tothe firm value of LQ45. The sample of this research is the LQ45 Company which is listed in Indonesia StockExchange in 2011-2015 periods. The total sample research is 20 company which has been determine by usingpurposive sampling. The analysis method from this research has been done by using multiple regressionsanalysis technique. The result of this research shows that: (a) managerial ownership has positive influence to thefirm value because the existence of managerial ownership will decrease agency conflict in the company; (b)institutional ownership has positive influence to the firm value because the ownership becomes monitoringmechanism which guarantees the enhancement the prosperity of the stockholders.(c) independent commissionerhas positive influence to the firm value because the large numbers of the members of independent commissionerreflects that commissioner has conducted supervision and they are in a good coordination and in maintaining thebalance of the majority and the minority of stockholders; (d) the ROA has positive influence to the firm valuebecause when the ROA is getting high, it shows good financial performance; (f) firm size does not have anyinfluence to the firm value because firm size is not an important factor in investing.Keywords: Good Corporate Governance, Financial Performance, Firm Size, Firm Value.